Basic and functional characterization of the Peruvian Hairless Dog semen - Santiani, Alexei (2020)
The aim of this study was to characterize the semen of the Peruvian Hairless Dog. Fifteen males, aged 1 to 5 years, registered by the Kennel Club Peruano were used to collect semen (one ejaculated per male) by digital manipulation. A basic spermatogram was performed and macroscopic (volume and colour) and microscopic (sperm motility and concentration, using light field microscopy) characteristics were recorded. Additionally, sperm function tests were performed: sperm viability (using SYBR-14 and propidium iodide), mitochondrial membrane potential (MMP, using MitoTraker Deep Red FM), and acrosomal integrity (using FITC-PSA and propidium iodide) and analysed by flow cytometry with image analysis. The following values ​​were found (mean ± 95% CI): 6.1 ± 2.7 ml volume, opalescent colour; 66.7 ± 10.5% motility; 262.7 ± 20.4 x 106 sperm/ml sperm concentration; 77.7 ± 9.7% of sperm viability; 85.9 ± 5.1% high MMP; 83.6 ± 14.9% acrosomal integrity. These results represent the first report on the seminal characteristics of this breed and could be taken as reference values ​​for a better selection of breeding males and for the diagnosis of reproductive alterations of the breed.